Exploring Montessori Teachers' Differentiation Practices to Address Student Diversity - Febriyanti, Karina (Fakultas Ilmu Budaya, Universitas Brawijaya, 2026)
Montessori classrooms are widely recognized for supporting individualized learning; however, limited research has examined how these practices align with the framework of differentiated instruction (DI). This study addresses this gap by investigating the extent to which DI is evident in Montessori upper elementary English classrooms. A qualitative case study design was employed using semi-structured interviews with two Montessori English teacher working in mixed-age classrooms. Data was analyzed through thematic analysis using Tomlinson’s differentiated instruction framework as an analytical lens. The findings indicate that differentiated instruction is strongly present in practice but emerges as an implicit and experience-based approach rather than a formally planned instructional strategy. Teachers reporting adjusting instructional delivery based on readiness, providing individualized scaffolding, implementing flexible grouping and peer tutoring, and using continuous informal assessment to guide pacing and mastery-based progression. However, evidence of product differentiation was limited, as students generally demonstrated learning through similar output formats. The study concludes that differentiation in Montessori classrooms is structurally embedded within Montessori pedagogy, particularly through mixed-age grouping, student autonomy, and observation-based teaching. These findings suggest that differentiated instruction can develop organically through pedagogical design, offering insights for educators seeking to support learner diversity without relying solely on formal DI frameworks. Keywords: Montessori education; differentiated instruction; learner diversity; mixed-age classroom; individualized learning